TECHNOLOGY CHALLENGES IN ELT PROCESS DURING AND POST THE PANDEMIC IN RURAL AREA - Billik, Marthisa Olivia; Olbata, Yabes (Universitas PGRI Sumatera Barat, 2022)
Our education world is facing a very different situation due to the Covid-19 pandemic where these last few years, teaching and learning activities must be done online. However, the implementation of English online learning in remote areas did not go well due to the lack of teachers' and students’ ability in using technology in learning English during and post the pandemic. Therefore, the study was conducted to see how the correlation between the teachers’ competence, students' attitude, and the rural environment in affecting the use of technology in the English teaching and learning process during and post-pandemic. In this study, interview and observation were conducted to collect the data. The result of the study showed that there were some correlations between the rural environment, students’ attitudes, and teachers’ competence in facing the technology challenges in learning the English process during and post the pandemic. Teachers and students were difficult to adjust with the use of technology due to limited facilities in a rural area, lack of skill in using the technology, and negative attitudes that decrease students' motivation in learning English during the pandemic. However, improvement was also found in the post-pandemic, where the students and teachers could improve their competence in using technology media in learning English. The result showed that the students showed high motivation when the teacher delivered material and gave assignments using technology. Furthermore, teachers are also able to improve their teaching competence in creating teaching media based on technology use in the post-pandemic.